Monotypic colonies of Clathropteris meniscioides (Dipteridaceae) from the Early Jurassic of central Patagonia, Argentina: implications for taxonomy and palaeoecology - Choo, Thereis Y.S. (2016)
A collection of over 130 specimens of the fossil dipterid fern Clathropteris meniscioides (Brongn. 1825) Brongn. 1828 from in-situ colonies in the Lower Jurassic of Chubut, Argentina, provides evidence for population-level morphological variation within the species and palaeoecology of the site. Characters such as angle of insertion of secondary veins, tertiary vein arrangement and tooth depth were observed to vary between specimens, and the total range of variation captured by this population was found to overlap and intergrade with the descriptions of several previously identified Clathropteris species. This suggests that species delimitations based on minor differences in such characters should be regarded with skepticism, and that the current number of species ascribed to this genus may be artificially inflated. Abundant C. meniscioides fossils at different development stages buried together in a single, thick bed of sheet-flood deposits provide evidence for the species having formed large, pure colonies in open, disturbed floodplain areas. The characteristic and extremely high leaf-vein densities would have allowed for greater carbon assimilation and rapid growth rates. Altogether, this suggests that the species was a fast-growing pioneer species of floodplains, a prominent part of the Early Jurassic vegetation in Gondwana, and a likely food source for large herbivorous dinosaurs common at that time.